A comparative study on the physicochemical properties, reactivity and long-term performance of sulfidized nanoscale zerovalent iron synthesized with different kinds of sulfur precursors and procedures in simulated groundwater. (1st April 2022) - Xiao, Shuangjie; Jin, Zilan; Dong, Haoran; Xiao, Junyang; Li, Yangju; Li, Long; Li, Rui; Chen, Jie; Tian, Ran; Xie, Qianqian
Highlights: Aging and Long-term reactivity of S-nZVI were evaluated in simulated groundwater. Sulfidation sequence can control the crystallinity of Fe 0 and sulfur species. Sulfur precursors can affect the evolution of sulfur speciation in groundwater. Sulfur reagents and sulfidation sequence did not alter the TCE degradation pathway. The degradation product distribution was affected by the aging of S-nZVI. Abstract: There are plentiful ways to synthesize sulfidized nanoscale zerovalent iron (S-nZVI), and this study investigated the influence of sulfur reagents (Na2 S, Na2 S2 O3, Na2 S2 O4 ) and sulfidation sequence (co-sulfidation and post-sulfidation method) on the physicochemical properties, reactivity, and long-term performance of S-nZVI in simulated groundwater. The results suggested that the co-sulfidized nZVI (S-nZVIco ) has higher reactivity (∼2-fold) than S-nZVIpost due to the stronger electron transfer capacity, deriving from the higher content of Fe 0 and reductive sulfur species. However, during aging, the reactivity of S-nZVIco would be lost more rapidly than S-nZVIpost, due to the faster corrosion of Fe 0 and more oxidation of reductive sulfur species. S-nZVIpost has the superior long-term performance with the degradation rate of trichloroethylene (TCE) remained at 30%∼60% even after 90 d of aging. Sulfur precursors can control the selectivity of S-nZVI by affecting the sulfur speciation on the particle surface. The proportion of reductive sulfur species on S-nZVIpost synthesized by Na2 S was higher than S-nZVIpost synthesized by Na2 S2 O3 or Na2 S2 O4, resulting in a higher selectivity of the former S-nZVIpost than the latter S-nZVIpost . In addition, sulfidation procedures and sulfur precursors did not affect the degradation pathway of TCE. Nevertheless, the degradation product distribution can be affected by the different physicochemical transformation of various types of S-nZVI with the aging time. These results indicated that sulfur reagents and sulfidation procedures have crucial effects on the reactivity and long-term performance of S-nZVI, which can be designed for the specific application scenarios. Graphical abstract: Image, graphical abstract